Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2020)
This paper analyses a range of literature reviews to identify characteristics of effective teacher education, including focusing on practical subject pedagogy; incorporating peer support and; creating a coherent policy environment.
previousDOI: 10.5281/zenodo.4762301 previousDOI: 10.5281/zenodo.3873462 EdTechHub.Copy: 2129771:237CSM4W EdTechHub.Copy: 2129771:237CSM4W KerkoCite.ItemAlsoKnownAs: 2129771:237CSM4W 10.5281/zenodo.3873462 10.5281/zenodo.4762301 10.53832/edtechhub.0007 2129771:237CSM4W 2129771:RMWSKUI5 2339240:2Y5CD84V 2339240:4P99D7MN 2339240:5P9STQIK 2339240:8DMB3N8E 2339240:AQFSE6DQ 2339240:K3RVT7JU 2339240:WP59YJ57 2339240:ZV7A4BWS 2405685:3T894KD8 2405685:3TKLS2TH 2405685:3UXB7ZWR 2405685:BHY8AJBY 2405685:I62EYSDT 2405685:LNUMVYFV 2405685:P5MEX8KB 2405685:R9VVKUH5 2405685:T48HFJM4 2486141:IX4B74H9 2534378:T2X9U5AV
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _forthcoming; _zenodoETH:submitted; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Characteristics of effective teacher education in low- and middle-income countries: an annotated bibliography (HDR10C) - McBurnie, Chris; Allier-Gagneur, Zoe; Haßler, Björn (EdTech Hub, 2020)
previousDOI: 10.5281/zenodo.3873460 EdTechHub.Copy: 2129771:3AV78BC7 EdTechHub.Copy: 2129771:3AV78BC7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3873460 10.53832/edtechhub.0008 2129771:3AV78BC7 2339240:FE5LM4QS 2405685:KXY7Q6VT
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
ZenodoArchiveID: 5652128 previousZenodoArchiveID: 3885817 previousshortDOI: 10/ghgngv previousshortDOI: 10/ghgngv previousDOI: 10.5281/zenodo.3885817 previousshortDOI: 10/ghgngv EdTechHub.Source: 2405685:HE2Q6Z8Y EdTechHub.Source: <this> shortDOI: 10/ghgngv KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 10.53832/edtechhub.0018 10/ghgngv 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y 2405685:SRU74BP6
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode